Reducing Verbal Aggression in Early Childhood through the Development of the “Menjaga Lisan” Storybook - Denok Dwi Anggraini; Muthi’ah Muthi’ah; Adhisa Ayuning Tyas; Dwi Fatmawati; Layina Humairo (Kindergarten: Jurnal Pendidikan Anak Usia Dini Indonesia, 2025)
Verbal Aggression in early childhood is a form of unwanted behavior that often occurs in the school, home,or playground environment. Actions such as shouting, insulting, or swearing at peers if left without proper intervention, these behaviors can have a negative effect on society. Someone who has this character can disrupt the environment around the child. The development of the book “Menjaga Lisan” aims to reduce verbal aggression in children with a comprehensive approach and based on ethical values. The type of observation or research used is Research and Development or often known as RnD. The RnD method is a research method used to create a product which is then tested for its effectiveness. The subjects of this study were 9 children aged 6 years at one of the kindergarten institutions in Ponorogo Regency. The results of statistical analysis calculations show that the use of the “Menjaga Lisan” guidebook with the storytelling method is effective in reducing verbal aggression in children. This finding supports the research hypothesis that storytelling based interventions can have a positive impact on controlling verbal aggressive behavior in early childhood. After the trial was carried out for 3 days, there was a positive increase in children, such as children's awareness in speaking, the formation of positive habits by speaking more politely, and not speaking rudely, children can respect other people's feelings more, children can communicate well and respect others more, and children also learn to control their emotions.